Mental Health and Mental Health Literacy: Importance and Challenges in the UAE - Mughis, Fatima (2022)
Background: Today almost 20% of the world population suffer from some type of mental illness. Despite mental health issues not being uncommon, there is a persisting stigma that is attached to the topic of MH due to the lack of literacy related to it, particularly in the non-Western and Arab regions of the world. Objective: This study was conducted in order to highlight the importance of mental health as a topic of interest within the UAE, as well as mental health literacy as a good method of supporting the general population. It also attempted to view certain determinants of MH and MHL. Method: A comprehensive literature review was done, and a survey was digitally distributed to collect demographic, health and literacy data. Analyses were done on the collected data. Results: Literature proved to back the hypothesis that not only is MH and MHL important, efficient and beneficial worldwide, but it is also so in the Arab world specifically. Certain prior results were replicated and supported in terms of the sample (n=74) collected. Conclusion: The UAE can potentially use lessons from other countries to build on with regard to policies and interventions being chosen for implementation within the country. The work done in this study, while descriptive, can be used as a foothold and as encouragement for future studies.